The Effect of Cow Manure Application on the Growth and Production of Cucumber Plants (Cucumis sativus L.) - Jusnita Siregar; Wahyuni, Siti Hardianti; Jumaria Nasutiom (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2024)
Cucumber (Cucumis sativus L.) is one of the vegetable plants that has many benefits, namely besides being able to be used as vegetables, fresh vegetables, salads or pickles, cucumbers are also beneficial for health because the nutritional value of cucumbers is quite good as a source of minerals and vitamins. Efforts to increase cucumber plant production can be influenced by many factors, one of which is fertilization. Fertilization is a determining factor in efforts to increase the availability of nutrients for plants, thus the expected impact of fertilization is not only to increase the yield per unit area but also to be efficient in the use of fertilizers. The method in this research is Non Factorial Randomized Group Design with four treatments and six replications, namely A0 (Control), A1 (Cow dung manure dose of 3 kg / polybag), A2 (Cow dung manure dose of 5 kg / polybag) and A3 (Cow dung manure dose of 7 kg / polybag). The results showed that the treatment of cow dung manure gave a significant effect on the parameters of plant height and fruit weight. The best treatment is found in A3, which is the application of cow dung manure at 7 kg/polybag.